Information and communication technologies' knowledge and use by Health Technology teachers - Rafaela Nayibe Curi Mendoza (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation: information and communication technologies are tools and methods used to collect, retain, manipulate or distribute information. Its use in educational processes is blocked by various reasons, but training in this field is of great importance. Objective: to characterize the knowledge and use of information and communication technologies by Health Technology teachers. Methods: a descriptive, observational and cross-sectional study was carried out. The studied population was the Department of Health Technology's professors of the Victoria de Girón  Basic and Preclinical Sciences Institute  in 2021. Summary measures were used for the variables according to their nature. Results: 60% of teachers with 5-10 years of experience were obtained. 33.4% received training in the use of technologies; and 26.6% used them. 45.6% acquired their knowledge self-taught. 83.3% reported that the use of these media improves the quality of teaching. Conclusions: most of the participating teachers have experience of 5-10 years in their work, and few have been trained in the use of information and communication technologies; however, they consider that they are useful as a complement to conventional teaching methods and improve the quality of teaching, prevailing interest in improvement courses.